El rincón sensorial para estimular los sentidos en los infantes del subnivel de Educación Inicial. - Esquivel Zambrano, Silvana Estefanía (2020)
The purpose of this degree project is to achieve the research and development in the "Vicente León" elementary school therefore, through this intermediate seeks to have an adequate and appropriate space that facilitates infants a correct development, its objective is to implement the corner sensory to stimulate the senses in children of the initial education level sublevel 2, always seeking the well-being and correct learning of infants from 4 to 5 years old. The methodology of the present investigation begins from a Quantitative approach, then, part of the deduction, because it is based on the search for an existing theory, in addition, it is tested in the educational reality and the approach is structured, predetermined, formal and specific. Also has a feasible project research modality as it contains sources bibliographies, field research and the proposed proposal. Once endorsed the proposal by experts on the subject of training projects of research and development it can be said that mentioned project is feasible and their execution may be carried out once the health emergency is over decreed by the national government, at the same time, it is important to mention that great utility and support in institutional development thanks to its great contribution practical and utilitarian in childhood welfare, therefore, the development of their skills and abilities, with adequate space